(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This research aims to address the sanctions that may be applied to the President of the Republic in a public civil action of administrative misconduct. First, an approach was made about the passive subjects of acts of misconduct. Subsequently, an analysis of the legal nature of the administrative misconduct action was performed, using the explanatory research method, and a comparison with other countries in opposing positions in the ranking of the non-governmental organization Transparency International (TNI). In the end, it is concluded that the legislature was careful to place the President of the Republic in a different position from other public officials. KEYWORDS: Administrative misconduct. President. Responsibility.